The Competitiveness of Thai Durian Export Enterprises to China: A Case Study of HKK Trading & Processing Co., Ltd. - Liu, Wanglin; Rojsuwan, Bavornwit (Rajapark Journal, 2025)
This research aimed to (1) analyze the competitive strategies of HKK Trading & Processing Co., Ltd. in the Chinese durian market, (2) identify strategies for enhancing the competitiveness of Thai durian export companies, and (3) evaluate the challenges and opportunities for HKK in expanding its market share in China. The study employed a case study methodology using qualitative interviews and multi-criteria decision-making tools, including SWOT and Analytical Hierarchy Process (AHP) analysis. The AHP sample consisted of five key customers located in China who had consistently purchased from HKK between 2021 and 2024. Their input was used to determine priority factors influencing supplier selection. The findings reveal three key insights. First, the recommended strategic direction emphasizes expanding marketing channels in China by leveraging the firm’s technological expertise in vacuum freeze-drying. In this area, HKK has accumulated over a decade of experience. Second, the AHP evaluation, based on the 7Rs logistics framework, yielded a consistency ratio of 0.07, confirming acceptable reliability. Among the criteria, “Right Quality” (Product Quality as Required) was ranked as the highest priority with a weight of 0.187, followed by “Right Source” and “Right Service.” Third, while HKK demonstrates strong internal competencies and technological differentiation, sustaining its market position requires a proactive approach to emerging external threats. These include increasing regional competition, rising logistics costs, and evolving consumer expectations. The company must enhance operational efficiency, ensure sustainable sourcing practices, and continually refine its strategic planning to maintain its leadership in the premium durian export segment.